Chimeric Flaps and “Their Variations”: Different Options for Immediate Reconstruction of Massive Facial Defects - Horta, Ricardo; Valença-Filipe, Rita; Monteiro, Diana; Silva, Alvaro; Amarante, José Manuel (Facial Plastic Surgery, 2014)
The reconstruction of massive head and neck defects is a difficult challenge, requiring restoration of bone, skin, and oral lining. Their complex three-dimensional nature often dictates the need of more than a single osteocutaneous flap for intra- and extra-oral reconstruction.Conventional reconstructive options can be considered, but there is no single ideal osteocutaneous free or pedicled flap providing an unlimited length of bone and skin paddle, or that could orient the skin paddle independently of the vascularized bone. The surgeon should then be aware of more complex options for reconstruction of extensive three-dimensional defects, namely chimeric free flaps and “their variations.” They can be stratified in three types, either based on their intrinsic vasculature—perforated-based, branch-based, or whether they are prefabricated (surgical junction by microanastomosis).Despite morbidity and not perfect matching in terms of skin texture and pliability, these techniques are a good alternative in the presence of partial defects, especially in the context of immediate oncological reconstruction, where facial transplantation is not considered.
Keywords: massive defects; facial reconstruction; chimeric flaps; flow-through free flaps